University students’ experiences of fully online teaching and learning environment—differences among learning profiles - Haarala-Muhonen, Anne; Asikainen, Henna; Katajavuori, Nina; Kinnunen, Päivi; Ripatti-Torniainen, Leena; Tuononen, Tarja (Frontiers in Education, 2025)
This mixed-method study explores university students’ experiences of fully online teaching–learning environments and their relations to students’ approaches to learning profiles. Altogether, 504 students from different faculties completed questionnaire measuring approaches to learning and responded to an open-ended question about their experiences with online teaching–learning environment. A mixed-method approach was chosen to provide a comprehensive understanding of students’ experiences by combining quantitative measures of learning profiles with qualitative insights into their perceptions. The qualitative responses were analysed using content analysis, while students’ learning profiles were identified using K-means clustering and differences between the profiles were examined with a chi-square test. The results show that fully online teaching was experienced rather positively, and it was considered convenient. However, most of the learning experiences were negative making online studying and learning challenging. Three approaches to learning profiles emerged from the data. Deep and organised students clearly had more positive experiences of online learning and studying than the Unorganised and deep students. The All-high students experienced online teaching most positively, while they had more challenges in learning. The results show that the implementation of fully online teaching has not supported enough collaboration and communality, leading to various challenges. In addition, there is a pressing need for better-designed assignments, more constructive feedback from teachers, and enhanced support for students’ study practices. These findings underscore the importance of viewing online teaching and learning as a holistic experience that profoundly influences students’ academic success and overall educational journey.